Self-Determination and Entrepreneurship with Motivation Support: Empirical analysis with university students of the administration course - Bizarria, Fabiana Pinto de Almeida (2019)
The research investigates the influence of Academic Motivation on Entrepreneurial Motivation, based on the relation of the seven dimensions of the Academic Motivation Scale (Demotivation, External Regulation, Introduced Regulation, Identified Regulation, Motivation to Experiment, to Realize and to Know) in Entrepreneurial Motivation. A sample of 245 university students from seven higher education institutions in three cities of the Northeast were used. The hypotheses were measured using a structural model, estimated by the Partial Least Squares Path Modeling (PLS-PM) method. The results pointed out the positive relationship between Academic Demotivation, as well as the dimensions of Extrinsic Motivation (External Regulation and Introduced Regulation), to Entrepreneurial Motivation. It is believed that the study potentially moves towards considering that learning does not provide real expectations and motivations for academics to undertake. The study suggests that courses and programs, aimed at entrepreneurship training, should lead to their objectives in order to shape students' previous motivations to achieve greater pedagogical effectiveness.